Sediment Radioactivity Levels of Deep-Water Fishery Grounds in Antalya Bay - Süleyman Fatih Özmen; Olgaç Güven (Aquatic Sciences and Engineering)
To evaluate the radiological load of the fisheries ground sediments of deep-water areas in the Antalya Bay, 226Ra, 232Th, 40K and 137Cs activity concentration levels were measured with the Gamma Spectroscopy technique using a HighResolution Germanium Detector (HPGe). Sediment samples were collected from the seabed surface of five different depth ranges (between 400 – 800 m). Detected mean radionuclide activities of 226Ra, 232Th, 40K and 137Cs were 16.53±2.41, 17.9±2.54, 371.44±18.44 and 3.91±1.27 Bq kg-1, respectively. The effect of the Chernobyl Nuclear Power Plant disaster in deep water sediments of Antalya Bay was observed. However, the detected radionuclide concentrations are at acceptable levels according to the International Atomic Energy Agency (IAEA).